2023
DOI: 10.1177/09731296221137378
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein Ameliorates Cerebral Ischemic-reperfusion Induced Neuroinflammation in Wistar Rats via Inhibiting NF-κB Signaling Pathway

Abstract: Background Cerebral ischemia is a condition of acute brain damage due to the depletion of oxygenated blood supply to cerebral tissues. Daidzein is an isoflavonoid predominantly present in soya, Pueraria species, and red cloves. Traditional Chinese medicine utilizes daidzein to alleviate diseases such as inflammation, hyperglycemia, gastric diseases, allergies and aches. The neuroprotective effect of daidzein on cerebral ischemic conditions and its mechanism of action was not yet elucidated. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…You et al investigated that Schisandrin A inhibit the RhoA/ROCK1 pathway to promote pulmonary capillary endothelial ( 23 ). Other study found that Schisandrin A recovered erectile dysfunction through regulating RhoA/ROCK1 pathway in type 1 diabetes mice ( 24 ). However, the regulatory role of Sch.…”
Section: Discussionmentioning
confidence: 95%
“…You et al investigated that Schisandrin A inhibit the RhoA/ROCK1 pathway to promote pulmonary capillary endothelial ( 23 ). Other study found that Schisandrin A recovered erectile dysfunction through regulating RhoA/ROCK1 pathway in type 1 diabetes mice ( 24 ). However, the regulatory role of Sch.…”
Section: Discussionmentioning
confidence: 95%